INDUSTRIALIZATION AND DE-INDUSTRIALIZATION IN INDONESIA 1983-2008: A KALDORIAN APPROACH - Priyarsono, D.S.; Lestari, Titi Kanti; Dewi, Diah Ananta (Journal of Indonesian Economy and Business, 2010)
Economists have for a long time discussed the causes of economic growth and theÂ mechanisms behind it. Kaldor viewed advanced economies as having a dual nature verysimilar to that of developing countries, with an agricultural sector with low productivityÂ and surplus labour, and a capital intensive industrial sector characterized by rapidÂ technical change and increasing returns. The transfer of labour resources from theÂ agricultural sector to the industrial sector depends on the growth of the latterâs derivedÂ demand for labour. With this background this study attempts to show the periods when theÂ Indonesian economy indicated the processes of industrialization and deindustrialization. Italso attempts to identify whether the economy experienced positive deindustrializationÂ (i.e., showed signs of economic maturity where service sector substituted the role ofÂ industrial sector as the engine of growth) or negative deindustrialization (i.e., showedÂ signs of economic stagnancy where industrial sector could not grow rapidly enough toÂ absorb surplus labour from agricultural sector). Lastly, this study attemps to analyzeÂ several factors that might be responsible for the process of the deindustrialization.Keywords: industrialization, deindustrialization, economic growth